PHYSICAL EDUCATION - DISCIPLINE OF STUDENTS ’CHOICE AS A COMPONENT OF THE VARIABLE PART OF THE EDUCATIONAL PROGRAM - Зюзь, Владимир; Бабич, Татьяна; Балухтина, Валентина (SWorldJournal, 2021)
Disciplines chosen by applicants are one of the components of the variable part of the educational program. Teaching elective subjects is one of the means of individualization of learning, development of initiative and independence of students. Elective c